EKSPANSI MINISO JEPANG KE INDONESIA STUDI KASUS: PEKANBARU 2019-2020 - Sahri Rafika; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The phenomenon of Miniso's expansion is an interesting phenomenon to study, because in marketing its products Miniso first examines the market and consumers, and the products offered contain a